Iranian EFL Teachers’ Understanding and Beliefs of Critical Pedagogy: A Multiple Case Study - Esmaeel Ali Salimi; Meysam Khazaee Kouhpar (Journal of Modern Research in English Language Studies, 2024)
Critical Pedagogy (CP) in Iran, among other countries, is still in its early stages, and there are various challenges facing the implementation of problem-posing education. To pinpoint the probable factors impeding transformation in the educational setting, the present research, using a convenience sampling, investigated 64 Iranian EFL teachers’ beliefs and understanding of CP and its fundamental tenets. Furthermore, attempts were made to examine the way these teachers’ understanding of CP informed their beliefs of it. As such, a set of interviews as well as observations were conducted to capture the participants’ statements, intention, and behavior. As a result of a thorough thematic analysis, it was discovered that approximately 89 percent of the 64 EFL teachers participating in this study did not have a profound understanding of this approach. This finding can bear witness to the inefficient or insufficient pre-service teacher education. Regarding their beliefs about CP, these EFL teachers either resisted or disagreed with the fundamental tenets of CP. The findings of the present study hold much to contribute to the related literature, insofar as new doors will be opened for those whose area of interest falls within the purview of CP and student voice.